Edukasi PIK-R Program GenRe Berbasis Sekolah Sebagai Tindakan Inovatif untuk Meningkatkan Pengetahuan Kesehatan Reproduksi - Nur Aini Dyah Prasetyaningrum; Sri Wahyuni; Tutik Rahayu (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Low knowledge of reproductive health among adolescents is characterized by an increase in premarital sexual behavior and limited access to information. The government, through the National Population and Family Planning Agency (BKKBN), developed the Generasi Berencana (GenRe) Program with the Youth Information and Counseling Center (PIK-R) based in schools as an effort to educate adolescents about reproductive health. Objective: This study aims to analyze the effectiveness of PIK-R education in improving adolescents' knowledge of reproductive health. The research design was quasi-experimental with a pre-post test with control group. A sample of 180 respondents was determined using purposive sampling and divided into intervention and control groups. The research instrument used a reproductive health knowledge questionnaire. Data analysis was performed using the Wilcoxon signed rank test and Mann-Whitney test. Results the study showed a significant increase in knowledge in the intervention group (p=0.000) after receiving PIK-R education compared to the control group (p=0.000). Education combined with board games and interactive counseling sessions proved to be effective in improving students' understanding and engagement in the learning process regarding reproductive health. Conclusion school-based PIK-R education has been proven effective in improving adolescents' reproductive health knowledge using an innovative approach.